2018
DOI: 10.1158/0008-5472.can-18-0988
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA CRYBG3 Blocks Cytokinesis by Directly Binding G-Actin

Abstract: The dynamic interchange between monomeric globular actin (G-actin) and polymeric filamentous actin filaments (F-actin) is fundamental and essential to many cellular processes, including cytokinesis and maintenance of genomic stability. Here, we report that the long noncoding RNA LNC CRYBG3 directly binds G-actin to inhibit its polymerization and formation of contractile rings, resulting in M-phase cell arrest. Knockdown of LNC CRYBG3 in tumor cells enhanced their malignant phenotypes. Nucleotide sequence 228-2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 43 publications
2
31
0
Order By: Relevance
“…LNC CRYBG3 is present in the human lung, brain, liver, and kidney, and is transcribed from the crystallin beta-gamma domain containing 3 (CRYBG3) gene on chromosome 3 (http://www.noncode.org/). In a previous study, we reported that LNC CRYBG3 directly binds to G-actin and suppresses G-actin assembly 19. Consistently, in the present study, unsupervised hierarchical clustering analysis of the expression of 1501 proteins showed that actin was the most downregulated.…”
Section: Discussionsupporting
confidence: 91%
“…LNC CRYBG3 is present in the human lung, brain, liver, and kidney, and is transcribed from the crystallin beta-gamma domain containing 3 (CRYBG3) gene on chromosome 3 (http://www.noncode.org/). In a previous study, we reported that LNC CRYBG3 directly binds to G-actin and suppresses G-actin assembly 19. Consistently, in the present study, unsupervised hierarchical clustering analysis of the expression of 1501 proteins showed that actin was the most downregulated.…”
Section: Discussionsupporting
confidence: 91%
“…In this regard, lncRNA CRYBG3 has been shown to interact with G-actin to inhibit its polymerization such that this interaction between CRYBG3 and G-actin blocks nuclear localization of MAL. A consequence is that SRF is kept away from the promoter region of several immediate early genes such as JUNB and Arp3 82 . Finally, direct interaction of lncRNAs with target proteins can also impact their nuclear trafficking.…”
Section: Post-transcriptional Regulation Of Gene Expressionmentioning
confidence: 99%
“…Regulating of cell cycle progression is another paramount mechanism to modulate tumor cell biological behavior (88). Various studies have reported divergent effects of BRACHYURY on cell proliferation.…”
Section: The Effect Of Brachyury On Tumor Cell Proliferation and Cellmentioning
confidence: 99%